Virtual reality experiential learning improved undergraduate students’ knowledge and evaluation skills relating to assistive technology for older adults and individuals with disabilities - Chen, Peng-Hsu; Ho, Hsuan-Wei; Chen, Hung-Chou; Tam, Ka-Wai; Liu, Ju-Chi; Lin, Li-Fong (BMC medical education, 2024)
The aging population has caused assistive technology (AT) to receive attention. Thus, ensuring accurate user comprehension of AT has become increasingly crucial, and more specialized education for students in relevant fields is necessary. The goal of this study was to explore the learning outcomes in the context of AT for older adults and individuals with disabilities through the use of VR experiential learning. A parallel-group design was used. Sixty third-year university students studying gerontology and long-term-care-related subjects in Taiwan were enrolled, with the experimental (VR) and control (two-dimensional [2D] video) groups each comprising 30 participants. Both groups received the same 15-minute lecture. Subsequently, the experimental group received experiential learning through a VR intervention, whereas the control group watched a 2D video to learn. The students' knowledge of AT was assessed using a pretest and posttest. Additionally, their skills in evaluation of residential environments were assessed using the Residential Environment Assessment (REA) Form for Older Adults. All data analyses were performed with SPSS version 22. In the posttest conducted after the intervention, the experimental group exhibited a significant 20.67 point improvement (p < 0.05), whereas the control group only exhibited improvement of 3.67 points (p = 0.317). Furthermore, the experimental group demonstrated a significantly higher score (+ 2.17 points) on the REA Form for Older Adults than did the control group (p < 0.05). VR experiential learning can significantly improve undergraduate students' knowledge and evaluation skills in relation to AT for older adults and individuals with disabilities.